Recovery of dense minerals as derivative in the exploitation of the alluvial terraces of the miño river (2010)
Times the main objective of this work is to define an industrial protocol to recover dense minerals present in the alluvial quaternary terraces of the Miño River (NW Spain), rich in a fine-grained and high-density material identified as black sands. The recovery and sale of these sands implies the complete utilization of the resource; thereby the sustainability of the exploitation is enhanced and the environmental costs are reduced. These black sands comprise two fractions of interest: a coarse-grained fraction, rich in gold, and a fine-grained fraction rich in monazite, ilmenite, zircon, garnets, rutile, andalucite and xenotime. On this second fraction, the methods to characterize the mineral grade from the chemical and mineralogical points of view were defined and the procedures to concentrate and recover these dense minerals were also established. As a result, the combination of dry techniques of separation with magnetic and electrostatic devices to treat the primary concentrate previously obtained from wet gravity concentration allowed the highest grade of the minerals of interest to be obtained.